2013
DOI: 10.1371/journal.pone.0059425
|View full text |Cite
|
Sign up to set email alerts
|

Elevational Gradient of Vascular Plant Species Richness and Endemism in Crete – The Effect of Post-Isolation Mountain Uplift on a Continental Island System

Abstract: Understanding diversity patterns along environmental gradients and their underlying mechanisms is a major topic in current biodiversity research. In this study, we investigate for the first time elevational patterns of vascular plant species richness and endemism on a long-isolated continental island (Crete) that has experienced extensive post-isolation mountain uplift. We used all available data on distribution and elevational ranges of the Cretan plants to interpolate their presence between minimum and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
123
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 78 publications
(113 reference statements)
19
123
1
1
Order By: Relevance
“…Incomplete sampling of environmental gradients can directly bias the resulting pattern. The present study confirms that species richness decreases with increase in altitude, in conformity with earlier studies (Bachman et al 2004;Jacquemyn et al 2005;Trigas et al 2013). With the increase in altitude, species diversity decreases as a result of environmental filtering, and because the higher altitude ecosystems have been mainly colonized by plant species tolerant of extreme weather conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Incomplete sampling of environmental gradients can directly bias the resulting pattern. The present study confirms that species richness decreases with increase in altitude, in conformity with earlier studies (Bachman et al 2004;Jacquemyn et al 2005;Trigas et al 2013). With the increase in altitude, species diversity decreases as a result of environmental filtering, and because the higher altitude ecosystems have been mainly colonized by plant species tolerant of extreme weather conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, our results on spatial distribution of plant species in the west Usambara Mountains are supported inding by Trigas et al [57] who reported an increase in proportion of plant species endemism with increasing elevation of Cretan Mountain that could only be explained by elevation-driven ecological factors. Ecologically, there are many factors coming into play, including temperature, rainfall, soils, and where human disturbances occur particularly deforestation, these leading to plant species extinctions in some area in the world [56].…”
Section: Vegetation Clearingsupporting
confidence: 90%
“…In Tenerife (Canary islands) altitude was the most important factor determining (inverse) patterns in endemic and native species along roadsides (Bacaro et al, 2015). Altitude itself is likely to be masking several long-term acting processes regarding endemism: the increased proportion of Cretan endemics with altitude is regarded as being due to diversification linked to the Cretan mountains (especially midaltitude areas), driven by altitudinal-driven ecological isolation (Trigas et al, 2013). Climate filtering reflected in varying patterns along altitudinal gradients is an important determinant of the richness of alien species (which are not adapted to high altitudes), while anthropogenic pressures may explain the richness of alien species at low elevation (Bacaro et al, 2015).…”
Section: Discussionmentioning
confidence: 99%